Increased Risk of Dementia in Patients with Tension-Type Headache: A Nationwide Retrospective Population-Based Cohort Study - Yang, Fu-Chi; Lin, Te-Yu; Chen, Hsuan-Ju; Lee, Jiunn-Tay; Lin, Chun-Chieh; Kao, Chia-Hung (PloS one, 2016)
The association between primary headaches, including tension-type headache (TTH) as one of the most common primary headache disorders, and dementia remains controversial. In this nationwide, population-based, retrospective, cohort study, we explored the potential association between TTH and dementia and examined sex, age, and comorbidities as risk factors for dementia. Using the Taiwan National Health Insurance Research Database (NHIRD) claims data, the sample included 13908 subjects aged ≥20 years with newly-diagnosed TTH in 2000-2006. The non-TTH group included 55632 randomly selected sex- and age-matched TTH-free individuals. All subjects were followed until dementia diagnosis, death, or the end of 2011. Patients with dementia, including vascular and non-vascular (including Alzheimer's) subtypes, were identified using International Classification of Diseases Ninth Revision, Clinical Modification codes. Multivariate Cox proportional hazards regression models were used to assess the risk of dementia and dementia-associated risk factors, such as migraine and other medical comorbidities. During the average follow-up of 8.14 years, the incidence density rates of dementia were 5.30 and 3.68/1,000 person-years in the TTH and non-TTH groups, respectively. Compared with the non-TTH group, the risks of dementia were 1.25 (95% confidence interval [CI], 1.11-1.42) and 1.13 (95% CI, 1.01-1.27) times higher in the women and >65-year-old TTH group, respectively. TTH patients with comorbidities had a higher risk of dementia. TTH patients had a greater risk of non-vascular dementia (hazard ratio, 1.21; 95% CI, 1.09-1.34) than the non-TTH group. TTH patients have a future risk of dementia, indicating a potentially linked disease pathophysiology that warrants further study. The association between TTH and dementia is greater in women, older adults, and with comorbidities. Clinicians should be aware of potential dementia comorbidity in TTH patients.